EVALUATION OF PERSONNEL INFORMATION SYSTEM HUMAN RESOURCES DEVELOPMENT AGENCY HUMAN RESOURCES TRANSPORTATION - Citra Handayani; Prihandoko Prihandoko (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
This study aims to determine the extent to which the personnel information system at the BPSDM of the Ministry of Transportation is running. This is done with the HOT FIT Model approach which tests several things on these variables including technology, Human, and Organization. As a result, the factory has a very large contribution of 63.6%. Based on these results, it can be concluded that the human factory element has a significant role, the thing that can be done is to provide regular training and continue to improve the quality of the Human factory.